PEMERANAN TEATER MAHASISWA ANGKATAN 2012 PADA PEMBELAJARAN TEATER: STUDI DESKRIPTIF ANALITIS - Rumadi, Hadi (Aksara Public, 2017)
The theater art is one of forms of the show drama and play focusing on acting. In addition, the development of theater is increasingly popular among student of Riau University especially student of Indonesian language education development. The reason is because the theater is part of the courses for students Indonesia language education department. Beside the theater, student is also equipped by knowledge such as poem, fairytale, rhyme, and pantun responses. The formulation of the problem is how student force 2012 to act the drama on theater lesson? The purpose of the research is describe and develop creativity and to see the effectiveness of student force 2012 in playing drama. Throught this research is expected to contribute about effectiveness of acting in theater that still need to be applied in the field of teaching literature. The overview of libraries investigating is theater theory and the indicator. The source of the data is four CD the appreances of the theater is staged in Januari 2015. The technique of collecting data is documentation technique.